Numerical Investigation of the Characteristics of the Dynamic Load Allowance in a Concrete-Filled Steel Tube Arch Bridge Subjected to Moving Vehicles - Qingfei Gao; Qilu Ma; Kemeng Cui; Jun Li; Chuang Xu (Shock and Vibration)
Dynamic load allowance (DLA) is a key factor for evaluating the structural condition of bridges; however, insufficient research has been performed regarding the characteristics of DLA in concrete-filled steel tube (CFST) arch bridges. To address this issue, based on an actual CFST arch bridge, the DLA characteristics of bridges are investigated numerically in this study. First, aiming at different structural components, such as the arch rib, main girder, and suspenders, the DLA values obtained at various locations of different structural components are compared in detail, and then the changing regulations of the DLA, considering the influence of different vehicle speeds and various extents of pavement roughness, are summarized and analyzed. Additionally, the relationship between the different DLAs obtained by using the different response indices, that is, displacement, bending moment, and axis force of structure, is investigated. Finally, some conclusions that are significantly beneficial for evaluating or detecting the condition of CFST arch bridges are drawn.